2004
DOI: 10.1046/j.1399-5618.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing the BALANCE trial – the role of the pilot study and start‐up phase

Abstract: Pilot studies and start-up phases are essential to refine clinical trial design and allow development of procedures that are both methodologically rigorous and flexible and robust enough to promote recruitment and follow up. BALANCE is now actively recruiting in the UK and USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The multi-center BALANCE (Bipolar Affective disorder: Lithium/ANticonvulsant Comparative Evaluation) trial has recently compared the effectiveness of valproate monotherapy, lithium monotherapy and lithium and valproate combination in maintenance treatment but at the time of writing the results are unavailable [53].…”
Section: Combination Of An Antipsychotic and Valproate In Maintenancementioning
confidence: 99%
“…The multi-center BALANCE (Bipolar Affective disorder: Lithium/ANticonvulsant Comparative Evaluation) trial has recently compared the effectiveness of valproate monotherapy, lithium monotherapy and lithium and valproate combination in maintenance treatment but at the time of writing the results are unavailable [53].…”
Section: Combination Of An Antipsychotic and Valproate In Maintenancementioning
confidence: 99%
“…BALANCE (bipolar affective disorder: lithium/anticonvulsant evaluation), funded by the Stanley Foundation, is an example of how such trials can be installed. After a run-in phase, during which they receive a combination of lithium and valproate for up to 8 weeks, patients will be randomized to receive lithium/valproate as monotherapy or combination treatment, and will be followed up for 2 years [90, 91]. The trial is open to any patient with bipolar disorder who agrees to commence maintenance treatment, but faces clinical uncertainty about the optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The BALANCE is a multicentre, UK and US, randomized trial comparing lithium, divalproex and lithium and divalproex in combination (42). The pilot study and start‐up phase have identified a number of pragmatic refinements to promote recruitment and follow‐up including: the dropping of masking (blinding) of participants and clinicians, the introduction of postal medication delivery and fewer follow‐up appointments (43). The study plans to randomize as many participants as possible before the end of 2005 and will assess whether the combination treatment arm is more effective in preventing hospital admission over a 2‐year period than either monotherapy.…”
Section: Discussionmentioning
confidence: 99%